Analisis Perubahan Iklim Bagi Pertanian di Indonesia - Grisvia Agustin; Ro'ufah Inayati (Jurnal Ekonomi dan Studi Pembangunan, 2015)
Agriculture sector will be adversly affected by climate change. And as a sector that absorbs the majority of  Indonesia’s employment impacts may be substantial. As the hydrological cycle is likely to be influenced b global warming, agriculture sector will have to adapt to this change. Moreover the impact on agriculture is closely linked to food security. The study aims to describe the climate change to Indonesia farmers that will result from the improved climate change management information in farming. The method used to analyze the climate change effect is descriptive method which presents economic data. The result shows that climate change reduce paddy filed and shifted the wet and dry seasons in many regions in Indonesia. The results of the study can be used by policy makers and the agencies involved in climate change information management.Keywords: climate change, farming, paddy field.